Improving the management of recurrent expenditures of the state budget in Dau Tieng district, Binh Duong province - Nguyễn, Chí Quang (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
This article studies the current situation of state budget recurrent expenditure management in Dau Tieng district, Binh Duong province in the period of 2017-2020 to point out shortcomings and limitations that need to be overcome. Specifically, focus on the following contents: (1) Preparation of state budget estimates; (2) Comply with state budget estimates; (3) Coordinate between tax authorities and functional agencies; (4) Structure of budget expenditure; (5) Inspection and examination of the state budget. From there, the strengths and weaknesses in the management of recurrent expenditures in Dau Tieng district are drawn. Thereby, the good sides to continue to maintain and promote, the bad sides to overcome and prevent. The article has proposed groups of solutions to improve the management of recurrent expenditures of the state budget in Dau Tieng district, Binh Duong province.